The relationship of practice exposure and injury rate on game performance and season success in professional male basketball - Caparros, T.; Alentorn-Geli, E.; Myer, G. D.; Capdevila, L.; Samuelsson, K.; Hamilton, B.; Rodas. G. (Journal of Sports Science & Medicine, 2016)
The objectives of this study were to determine the relationship among game performance, injury rate, and practice exposure in a professional male basketball team. A retroospective analysis of prospective collected data was conducted over seven consecutive seasons (2007/2008 to 2013/2014). Data collection included sports performance during competition (statistical evaluation), injury rate, and total exposure (games and practices). Over the surveillance period, 162 injuries (91 practice; 71 matches) occurred over 32,668 hours of exposure (556 games and 2005 practices). There was a strong positive correlation between: 1) exposure (total number of practices and hours of exposure) and the total number of injuries (r = 0.77; p = 0.04); 2) exposure (total hours of exposure and total hours of practice exposure) and performance (total team ranking) (r = 0.77 and p = 0.04, and r = 0.8 and p = 0.03, respectively); and 3) total number of injuries and performance (total team ranking) (r = 0.84; p = 0.02). While increasing practice and competition time is related to greater team performance, it also increases the number of injuries. However, higher injury rates were not associated with worse overall team performance. Efforts to reduce high-risk activity during practice, optimally replaced with injury prevention training, might help to reduce injury risk.